Measuring Rents and Interest Rate Risk in Imperfect Financial Markets: The Case of Retail Bank Deposits - Hutchison, David E.; Pennacchi, George G. (Journal of Financial and Quantitative Analysis, 1996)
Traditional measures of interest rate risk assume that prices of financial assets and liabilities are set in perfectly competitive markets. However, evidence suggests that many retail financial markets do not follow the competitive paradigm. In this paper, we employ a general contingent claims framework to value rents earned by banks in demandable retail deposit markets. Our analysis provides a natural and economically meaningful measure of interest rate risk for these imperfectly competitive markets. Using monthly survey data on NOW accounts and MMDAs, we estimate the value of retail deposit rents and deposit durations for more than 200 commercial banks.